(untitled) (Research, Society and Development, 2024)
Overweight and obesity, affecting about 60% of the adult population in Brazil, represent a growing public health issue. Driven by aesthetic standards, many people seek quick weight loss methods, resorting to diets and substances without professional guidance. In this context, plant-based compounds such as berberine, horsetail, garcinia, and morosil have gained prominence in compounded formulations for weight control due to their metabolic, lipolytic, antioxidant, and diuretic properties. This article aims to provide information about the products most demanded by the population and promote awareness about the rational use of weight loss formulations. This study analyzed the prevalence and composition of compounded formulations based on plant-based compounds in a pharmacy in the Municipality of Cascavel-PR, with dispensing data from January to December 2023. Among the 25 compounds evaluated, berberine was the most used (20.71%), and caffeine was the least frequent (3.0%). A seasonal demand was observed, with peaks in June and December, possibly influenced by cultural factors, and nutritionists were responsible for 51.52% of the dispensations. The analysis suggests that the high use of certain compounds reflects both market trends and patients’ perceptions of these components’ efficacy. However, using plant-based compounds without guidance can result in unwanted effects, underscoring the need for awareness of safe usage based on scientific evidence and professional supervision.